AN ANALYSIS OF ENGLISH EDUCATION STUDENTS' DIFFICULTIES AND PREFERENCES IN LEARNING GRAMMAR (A STUDY AT STAIN MAJENE) - Nuralima, Rizka; Afdaliah, Nihla; Uswatunnisa, Uswatunnisa (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This research examines the difficulties and learning preferences of English Education students at STAIN Majene in mastering grammar. Despite its significance for effective communication, Indonesian students face difficulties due to differences between Indonesian and English structures. Using a mixed-method approach, the research includes semi-structured interviews with 15 students from the 2021-2023 cohorts and a questionnaire distributed to all 70 students. Findings indicate that students struggle with environmental factors (lack of practice, limited class time), psychological factors (fear of judgment, varied perceptions of grammar's importance), and linguistic factors (material complexity, tense diversity). Students preferred active learning strategies, such as interactive videos and practical exercises. This highlights the need for educators to adapt teaching methods to address these difficulties and accommodate diverse learning preferences. Implementing engaging instructional strategies can enhance student comprehension and retention of grammar, offering valuable insights for improving English education programs and guiding future research.